Antibacterial Activity of Antimicrobial Peptide Indolicidin against Multidrug-Resistant Klebseilla pneumoniae Isolated from Patients with Burns - Noor Ibrahim Zaidan; Kais Kassim Ghaima; Hayder Mazin Rasool Al-Haboobi (Indian Journal of Forensic Medicine & Toxicology, 2022)
The emergence of multidrug resistant Klebsiella pneumoniae has become a significant problem worldwide and also being a major threat to patients with burns infections. The therapeutic action of antimicrobial peptides derived from humans or animals or synthetic peptides attracted attention as alternatives for antibiotics in order to treat the resistant strains especially with strains isolated from burn patients. The current study investigated the role of antimicrobial peptide Indolicidin as an antibacterial agent with multidrug K. pneumonia isolates from burns. The collection of study samples has taken place at the period between November 2020 and completed at end of March 2021, it has included 250 clinical specimens as burn swabs from inpatients with burn infections admitted in four hospitals in Baghdad. The results of selective media, biochemical tests, and Vitek2 system identified 40 isolates (16%) as K. pneumoniae from all collected bacterial cultures. The results of the antimicrobial susceptibility test by using the disc diffusion method for the isolates under study showed that K. pneumoniae clinical isolates were moderate resistant to the majority of the antibiotics tested. The majority of K. pneumoniae isolates were high resistant to Erythromycin (100%) and Ceftazidime (85%), also, it was obvious resistance to Ceftriaxone, Cefepime and Cefotaxime, while the lowest percentage of resistance was for Impenem (25%) and Meropenem (38%). The results of minimum inhibitory concentrations (MICs) of indolicidine against (10) K. pneumoniae isolates which multidrug resistant and formed the strong biofilm, revealed that range of concentrations of indolicidin was (0.7-100 µg/ml) and it was obvious that there is a significant effect of indolicdin on the growth of K. pneumoniae at very low concentrations. In this study, we believe that the development of these antimicrobial peptides may become a new generation of urgently needed antimicrobials that can overcome bacterial resistance mechanisms.